Genetic influence on eye movements to complex scenes at short timescales - Kennedy, Daniel P.; Bölte, Sven (Current biology, 2017)
Summary: Where one looks within their environment constrains one’s visual experiences, directly affects cognitive, emotional, and social processing [1, 2, 3, 4], influences learning opportunities [5], and ultimately shapes one’s developmental path. While there is a high degree of similarity across individuals with regard to which features of a scene are fixated [6, 7, 8], large individual differences are also present, especially in disorders of development [9, 10, 11, 12, 13], and clarifying the origins of these differences is essential to understand the processes by which individuals develop within the complex environments in which they exist and interact. Toward this end, a recent paper [14] found that “social visual engagement”—namely, gaze to eyes and mouths of faces—is strongly influenced by genetic factors. However, whether genetic factors influence gaze to complex visual scenes more broadly, impacting how both social and non-social scene content are fixated, as well as general visual exploration strategies, has yet to be determined. Using a behavioral genetic approach and eye tracking data from a large sample of 11-year-old human twins (233 same-sex twin pairs; 51% monozygotic, 49% dizygotic), we demonstrate that genetic factors do indeed contribute strongly to eye movement patterns, influencing both one’s general tendency for visual exploration of scene content, as well as the precise moment-to-moment spatiotemporal pattern of fixations during viewing of complex social and non-social scenes alike. This study adds to a now growing set of results that together illustrate how genetics may broadly influence the process by which individuals actively shape and create their own visual experiences.
Gesehen am 21.11.2018